2021
DOI: 10.1186/s12883-021-02343-0
|View full text |Cite
|
Sign up to set email alerts
|

Investigating novel biomarkers of immune activation and modulation in the context of sedentary behaviour: a multicentre prospective ischemic stroke cohort study

Abstract: Background Sedentary behaviour is associated with disease, but the molecular mechanisms are not understood. Valid biomarkers with predictive and explanatory properties are required. Therefore, we have investigated traditional and novel biomarkers of inflammation and immune modulation and their association to objectively measured sedentary behaviour in an ischemic stroke population. Methods Patients admitted to hospital with acute ischemic stroke we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…Associations between sedentary behavior and biomarkers of low-grade systemic inflammation have been reported for several chronic disease. 1,34 Altered levels of metabolites and proteins in trapezius and vastus lateralis muscle in patients with FM compared with healthy subjects have been reported previously using microdialysis. 18,20,32 Gerdle et al 20 reported significant muscle metabolic and blood flow alterations in this patient cohort compared with healthy controls, which may indicate muscle mitochondrial dysfunctions in FM.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Associations between sedentary behavior and biomarkers of low-grade systemic inflammation have been reported for several chronic disease. 1,34 Altered levels of metabolites and proteins in trapezius and vastus lateralis muscle in patients with FM compared with healthy subjects have been reported previously using microdialysis. 18,20,32 Gerdle et al 20 reported significant muscle metabolic and blood flow alterations in this patient cohort compared with healthy controls, which may indicate muscle mitochondrial dysfunctions in FM.…”
Section: Discussionmentioning
confidence: 71%
“…Associations between sedentary behavior and biomarkers of low-grade systemic inflammation have been reported for several chronic disease. 1 , 34 …”
Section: Discussionmentioning
confidence: 99%
“…As illustrated above, muscle movement plays a major role in KA production. A sedentary lifestyle will therefore unquestionably affect kynurenine metabolization ( Alme et al, 2021 ). Previous work showing that most KYN metabolites correlate with BMI ( Zahed et al, 2021 ) indicates that lifestyle influences tryptophan metabolism also at the level of food intake.…”
Section: Introductionmentioning
confidence: 99%